Eugenismo e seleção genética : a diversidade genética humana como bem jurídico-penal supraindividual - Conti, Paulo Henrique Burg (2017)
The main purpose of this work is to demonstrate that human genetic diversity constitutes a supraindividual interest, worthy of legal and criminal protection. Thus, in order to achieve this goal, a methodology of a deductive nature is used and a study of an interdisciplinary nature is carried out, encompassing several areas of knowledge: History, Biomedical Sciences, Bioethics and Criminal Sciences, with a special focus on Criminal Law. At first, the work seeks to determine that the use of modern genetic and reproductive technologies applied to the human being, cannot be based on an eugenics ideology of discriminatory character. Subsequently, in the bioethical analysis, the study aims to establish, as a support for the problematic scenario presented, a theoretical model based on the following principles: life, responsibility, and biomedical ethics (hierarchical). In the end, with the support of Constitutional Law and Criminal Law dogmatic, the thesis aims to determine that the sex selection and/or human genetic characteristics, in the non-therapeutic standpoint, violates constitutional principles and grounds the legitimation of legal and criminal intervention for the protection of human genetic diversity.